Pengaruh Gaya Kepemimpinan Transformasional, Kompensasi, dan OCB (Organizational Citizenship Behavior) terhadap Komitmen Organisasi Studi pada Karyawan Kantor Pos Besar Yogyakarta - Annisa Prihardita; Epsilandri Septyarini; Tri Ratna Purnamarini (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of transformational leadership style, compensation, and OCB (organizational citizenship Behavior) on the organizational commitment of the study of the Yogyakarta Post Office employees. This research was conducted at the Yogyakarta Post Office company located on Jalan Panembahan Senopati, Prawirodirjan, Yogyakarta, using 50 employees as research respondents. The sample research technique in this study was a census technique or saturated sampling. The results of the study show that transformational leadership styles, compensation, and OCB (organizational citizenship behavior) simultaneously influence Organizational Commitment.